2020
DOI: 10.1002/chir.23284
|View full text |Cite
|
Sign up to set email alerts
|

Candida antarctica lipase‐B‐catalyzed kinetic resolution of 1,3‐dialkyl‐3‐hydroxymethyl oxindoles

Abstract: Candida antarctica (CAL-B) lipase-catalyzed resolution of 1,3-dialkyl-3hydroxymethyl oxindoles has been performed to obtain (R)-1,3-dialkyl-3acetoxymethyl oxindoles with up to 99% ee and (S)-1,3-dialkyl-3-hydroxymethyl oxindoles with up to 78% ee using vinyl acetate as acylating agent and acetonitrile as solvent transforming (S)-3-allyl-3-hydroxymethyl oxindole to (3S)-1 0-benzyl-5-(iodomethyl)-4,5-dihydro-2H-spiro[furan-3,3 0-indolin]-2 0-one. The optically active 3-substituted-3-hydroxymethyl oxindoles and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 85 publications
(107 reference statements)
0
1
0
Order By: Relevance
“…Work by Chimni and co-workers demonstrated that enzymatic enantioselective acetylation of oxindole intermediates can be effected using an immobilised lipase from Candida antarctica (CALB). 56 Given some structural similarities between 11 and their substrates, we chose the same lipase to effect the resolution. Pleasingly, after screening a series of reaction conditions (see ESI † for details), 57,58 the racemic sample was successfully resolved, affording (−)-11 in 95% ee (determined by chiral HPLC) and 45% isolated yield together with acetate (+)-25.…”
Section: Papermentioning
confidence: 99%
“…Work by Chimni and co-workers demonstrated that enzymatic enantioselective acetylation of oxindole intermediates can be effected using an immobilised lipase from Candida antarctica (CALB). 56 Given some structural similarities between 11 and their substrates, we chose the same lipase to effect the resolution. Pleasingly, after screening a series of reaction conditions (see ESI † for details), 57,58 the racemic sample was successfully resolved, affording (−)-11 in 95% ee (determined by chiral HPLC) and 45% isolated yield together with acetate (+)-25.…”
Section: Papermentioning
confidence: 99%